The Impact of Technology Induced Professional Development Model on Coaching and Mentoring of Teachers - Christian Addai-Poku; Lawrence Sarpong; Desmond Allotey-Pappoe; Alexander Obiri Gyampoh; Benjamin Aidoo; Maxwell Bunu; Kwame Affro Oduro-Awisi (Noyam Journals, 2024)
The paper assessed the impact of technology-enhanced coaching and mentoring on the Continuous Professional Development (CPD) of teachers. It examined leveraging technology to build mentors' capacity, support mentees, and improve learning outcomes even with limited resources. The study explored the feasibility and effectiveness of a technology-enhanced training model in promoting CPD for mentors and enhancing teacher competencies in low-performing schools. A cross-sectional survey design was used, with questionnaires collecting data from 500 school improvement support officers (SISOs) in Ghana, selected through quota sampling. The data was analyzed using descriptive statistics. The results indicated that technology stimulates teachers' curiosity, intrinsic motivation, learning quality, and creative thinking. The study also found that technology-induced CPD is cheaper in the long term compared to traditional face-to-face models. However, many teachers face issues with internet connectivity and high data consumption, hindering access to online content despite having smart devices. The study recommends deliberate capacity building for teachers to improve their skills in accessing technology-enhanced CPD. It also suggests collaboration between governments, educational institutions, telecommunication companies, and internet service providers to make internet connectivity accessible and affordable. Exploring zero-rated data for teachers to access relevant content is also recommended.